Performance of newcomers in highly interdependent teams: the case of basketball teams - de la Torre-Ruiz, J. M.; Aragon-Correa, A. (European Sport Management Quarterly, 2012)
Sports teams have to continually change their player rosters in order to be competitive. As the hiring of new players is a high financial investment, team managers need to increase their understanding about newcomer performance.